Optimalisasi Peran Manajemen Purchasing dalam Pengadaan Barang untuk Menunjang Operasional Kitchen: Kasus di sebuah Resor di Ubud - Dewa Trinagata; Ida Ayu Kalpikawati; Ni Luh Gde Sri Sadjuni (Journal of Tourism and Hospitality Analysis (JoTHA), 2026)
This study aims to analyze the optimization of the role of purchasing management in the procurement of goods to support kitchen operations at a Resort & Spa in Ubud. The approach used is qualitative with three types of informants, namely key informants (Purchasing Supervisor), main informants (Chef) and supporting informants (Receiving Section). Data were collected through observation, interviews, and documentation studies and analyzed descriptively qualitatively including the stages of data reduction, data presentation, and conclusion drawing. The results showed that the role of purchasing has been running optimally, with the application of indicators that are in accordance with the theory and SOP. The process of procuring and receiving goods runs smoothly, thus supporting the smooth operation of the kitchen. However, the purchasing team faces obstacles such as late deliveries, mismatched goods and sudden requests. These obstacles can be overcome through effective communication between the purchasing team and the kitchen team.